Redefining Loyalty: A Qualitative Exploration of the Job-Hopping Paradox and Occupational Commitment in Generation Z - -, Stefanie Aurelia; Kuncoro Dewi Rahmawati (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2026)
Job hopping among Generation Z is frequently stigmatized as a crisis of organizational loyalty. However, traditional metrics that equate commitment with tenure fail to reflect the shifting values of the modern workforce. This qualitative study explores how Indonesian Gen Z employees navigate the tension between frequent career mobility and organizational commitment. Through in-depth interviews (N=6) with active job hoppers, thematic analysis reveals a critical paradox: while participants frequently exit organizations, they maintain robust occupational commitment, remaining steadfast in their professional fields. Our findings indicate that job hopping is not a rejection of responsibility but a strategic response to toxic leadership, excessive workloads, and career stagnation. For Gen Z, loyalty has transitioned from "where one works" to "how one works"—emphasizing integrity and professional identity over institutional longevity. This research challenges the "disloyalty" narrative and provides a roadmap for organizations to pivot from seniority-based retention to supportive environments that foster professional growth.